Effects of Preinterview Beliefs on Applicants' Reactions to Campus Interviews - Stevens, Cynthia Kay (Academy of Management Journal, 1997)
This study explored whether applicants' preinterview job beliefs affected their interview behavior and postinterview reactions. I obtained 106 pre- and postinterview applicant surveys and audiotapes of 24 interviews. Results indicated that applicants' preinterview expectancies correlated positively with their impression management tactics, confirmatory questions, and perceptions of recruiters. Perceptions of recruiters partially mediated pre- to postinterview job-belief relationships. Job-knowledge confidence and the expected total number of job offers moderated effects of preinterview beliefs on confirmatory questions. Research and practical implications are discussed.